Tracking over 30 years of coral reef infrastructure degradation in Barbados - Aliyah Griffith; Max Buglisi; Sandra Lee; Karl Castillo (Scientific Reports)
Abstract Coral reefs face escalating threats from global and local stressors, and these challenges are exacerbated in the Caribbean. This study focuses on coral reef structure in Barbados, where a previous study documented reef degradation in the 1990s. As 30 years have passed, we examined the rate of change of reef structure and quantified associated substrate presence along the western reefs of Barbados. Using satellite and geotagged imagery, we analyzed 19 reef structures over the interval 2013 to 2023 along the west coast of Barbados, comparing them to the previous study’s findings in 1950 and 1991. We ground-truthed five sites previously categorized as highly degraded reefs to confirm their structural integrity and substrate-type. Results confirmed ongoing reef structural loss, averaging ~ 137.68 m1 annually across all sites. We identified four primary substrate types: coral, algae-covered substrate, rubble, and sand, with algae-covered substrate predominating and projected to persist. Our results underscore the urgency of monitoring reef health and highlight the potential limitations of satellite assessment. This research enhances understanding of reef dynamics and offers a framework for identifying vulnerable areas, which are crucial for effective conservation efforts.